The Effect of Corporate Governance on Earnings Management with Capital Structure as Intervening Variable - Nur Meida Audina (Journal of Business and Management Review, 2020)
The purpose of this study is to determine the effect of corporate governance on earnings management with capital structure as an intervening variable in Islamic commercial banks registered in the Financial Services Authority (OJK) for the 2014-2018 period. This research uses quantitative research by using multiple linear regression and path analysis as data analysis. This study uses secondary data in the form of panel data on Islamic commercial banks registered with the Financial Services Authority (OJK) for the 2014-2018 period. The data that has been obtained is then analyzed using SPSS 23 devices. The population in this study are all Islamic commercial banks registered at the Financial Services Authority (OJK) during the 2014-2018 period. The sampling method is done by purposive sampling that is by using several criteria to obtain 12 Islamic banks that are used as research samples. The results of this study indicate that managerial ownership, institutional ownership and audit committee have no effect on earnings management. Managerial ownership, institutional ownership, and audit committee do not affect the capital structure. Capital structure cannot mediate the relationship between managerial ownership, institutional ownership and earnings management.